1999
DOI: 10.1099/00221287-145-9-2221
|View full text |Cite
|
Sign up to set email alerts
|

Green fluorescent protein as a reporter for spatial and temporal gene expression in Streptomyces coelicolor A3(2) This paper is dedicated to the memory of Kathy Kendrick, whose devotion to understanding the biology of Streptomyces was unsurpassed.

Abstract: The enhanced green fluorescent protein (EGFP) gene is a modified version of the green fluorescent protein gene of the jellyfish Aequorea victoria with a codon usage that corresponds well to that found in many GC-rich streptomycete genes. Here the use of EGFP as a reporter for the analysis of spatially and temporally regulated gene expression in Streptomyces coelicolor A3(2) is demonstrated. The EGFP gene was inserted into plasmids that can replicate in Escherichia coli, greatly facilitating the construction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
160
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(164 citation statements)
references
References 27 publications
4
160
0
Order By: Relevance
“…7). It is noteworthy that integration of pIJ8600 does not appear to affect growth or antibiotic production in S. coelicolor (Sun et al, 1999;Hesketh et al, 2001). Thus, the effects of integration may be species specific and our data suggest that experiments in which the wC31 attachment site is used for integration should always involve an analysis of the effects of integration on the physiology of the host organism.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…7). It is noteworthy that integration of pIJ8600 does not appear to affect growth or antibiotic production in S. coelicolor (Sun et al, 1999;Hesketh et al, 2001). Thus, the effects of integration may be species specific and our data suggest that experiments in which the wC31 attachment site is used for integration should always involve an analysis of the effects of integration on the physiology of the host organism.…”
Section: Discussionmentioning
confidence: 95%
“…Plasmids for overexpression of S. antibioticus pnp were constructed using the streptomycete expression vector pIJ8600 (Sun et al, 1999;Kieser et al, 2000). For the construction of pJSE340 a 3?2 kb PCR fragment was prepared, extending from the beginning of the intergenic region between a putative integral membrane protein and the rpsO gene upstream of pnp, to a BamHI site in a putative protease gene downstream of pnp (see Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the sigF gene, encoding the late-sporulation-specific σ F , is temporally committed to sporulation in both strains (Kelemen et al, 1996 ;Kormanec et al, 1996). Sun et al (1999) have recently shown that expression of sigF is spatially limited to the spore compartment, with no evidence of its expression before sporulation septa are formed in S. coelicolor. The dependence of sigF expression upon early-sporulation-specific σ factor gene whiG\rpoZ in both strains indicated a cascade of activation, similar to that occurring in B. subtilis (Kelemen et al, 1996 ;Kormanec et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…33 E. coliStreptomyces shuttle plasmid, pHZ1358 (provided by Dr Yinghua Zheng), was used to construct the nsdA gene-replacement vector. pIJ8600, which integrated into the S. bingchengensis_226541 chromosome by site-specific recombination at the bacteriophage FC31 attachment site, attB, 34,35 was used to introduce single copies of genes into the S. bingchengensis_226541 chromosome.…”
Section: Microorganisms Cloning Vectors and Cultivationmentioning
confidence: 99%